Surprised by Jesus again: reading the Bible in communion with the saints - Byassee, Jason (William B. Eerdmans Publishing Company, 2019)
No one expects to be surprised. Yet biblical interpretation can do exactly that. Christians expect to see Jesus as they read the Bible, but when and how Jesus actually speaks through Scripture can still surprise us! Drawing on the early church's theological giants -- Origen, Augustine, Gregory the Great, and more from the historical cloud of witnesses -- author Jason Byassee models how we can recover ancient Christians' multiple ways of reading the Bible to our benefit. As Byassee says, God himself is Jewish, Catholic, and Pentecostal -- so much larger than our own little corner on the truth -- and this book offers readers a refreshingly enhanced vision of the Bible and of Jesus himself